Quality of therapy and mental health among occupational therapists during the COVID-19 pandemic - Ayahito Ito; Ayahito Ito; Ayahito Ito; Daisuke Sawamura; Shogo Kajimura; Hideki Miyaguchi; Haruki Nakamura; Toshiyuki Ishioka (Frontiers Media S.A., 2022)
IntroductionThe coronavirus disease of 2019 (COVID-19) has had a severe psychological impact on occupational therapists. Clarifying the mental health status of occupational therapists and its relationship with therapy quality is essential for maintaining the quality of care and patients' quality of life. Therefore, the present study aimed to investigate whether and how mental health problems are related to the quality of occupational therapy.MethodsA nationwide cross-sectional online survey was conducted during Japan's second national state of emergency (January 2021). A total of 4,418 registered occupational therapists who were members of the Japanese Association of Occupational Therapists participated in this study. After screening for the exclusion criteria, data from 1,966 participants were analyzed.ResultsPath analysis showed that insufficient information provision by the workplace and increased workload were associated with depression, anxiety, and insomnia. Specifically, depression was associated with decreased therapy quality. Furthermore, one's therapy quality showed a strong positive correlation with colleagues' therapy quality.DiscussionThese results demonstrated a direct link between therapists' mental health conditions and therapy quality and suggested that decreased therapy quality might occur at the institutional rather than individual level. A reassessment of the support system and prompt detection and support for professionals with psychological symptoms may be the key to enhancing therapy quality and patients' quality of life. The present results contribute to the understanding of these relationships, considering the current pandemic context for occupational therapists.